ANALISIS SEMIOTIKA PADA POSTER LARANGAN ZINA DAN MAKSIAT DI TAMAN BATANG AGAM KOTA PAYAKUMBUH - Usdara` `'it; Desi Syafriani (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to find out the meaning of the semiotics contained in the posters prohibiting adultery and immorality in Batang Agam Park, Payakumbuh City. This type of research is qualitative, namely research that is not obtained using measurements but using words. This study uses Charles Sanders Pierce's semiotic analysis model known as the semiotic meaning of the triangle or known as the meaning of the triangle, namely icons, indexes, and symbols. The subject of this study was posters prohibiting adultery and immorality in Batang Agam Park, Payakumbuh City, whose information was obtained from key informants managing the posters, namely the Public Works and Spatial Planning Office of Payakumbuh City and supporting informants, namely tourists and regular traders.cFrom the results of the analysis of posters in Batang Agam Park, Payakumbuh City, it can be concluded that iconicly the similarities can be found in the use of images, indexially the use of non-formal language, short and easy to understand, and symbolically the meaning of the whole poster is an invitation not to selves close to committing adultery and immorality as prohibited by Islam. Keywords: Semiotic Analysis, Posters Prohibiting Adultery and Immorality